MENGGALI KEMBALI PEMIKIRAN KARL RAHNER TENTANG KEKRISTENAN ANONIM DAN KAITANNYA TERERHADAP GEREJA MASA KINI - Arthur Mangatur Lumbantobing (HYPOTHESIS : Multidisciplinary Journal Of Social Sciences, 2025)
This study aims to re-examine Karl Rahner’s concept of Anonymous Christianity and its relevance to the contemporary church within the reality of a pluralistic society. Rahner developed this concept in response to the question of salvation outside the church and the relationship between Christianity and other religions. In today’s world, marked by increasing religious diversity, the church is challenged to formulate a theological approach that promotes dialogue and tolerance while maintaining its Christian identity. This study employs a qualitative method with a library research approach. Data were analyzed descriptively and analytically through an examin ation of Rahner’s ideas, critiques of his thought, and their relevance to contemporary ecclesial life. The findings indicate that Anonymous Christianity represents a form of theological inclusivism that emphasi zes the universality of God’s grace. Although salvation remains cente red in Jesus Christ, Rahner argues Christ’s saving grace can also reach non-Christians. In Indonesia, this concept offers a theolog ical foundation for interreligious dialogue, inclusive ministry & the prom otion of tolerance, peace, & cooperation among religious community